pytopicgram: A library for data extraction and topic modeling from Telegram channels - Juan Gómez-Romero; Javier Cantón Correa; Rubén Pérez Mercado; Francisco Prados Abad; Miguel Molina-Solana; Waldo Fajardo (SoftwareX)
Telegram is a popular platform for communication, generating large volumes of messages through its open channels. pytopicgram is a Python library designed to help researchers efficiently collect, organize, and analyze Telegram messages, addressing the increasing demand to understand online discourse. Key functionalities include efficient message retrieval, computation of engagement metrics, and advanced topic modeling. By automating the data extraction and analysis pipeline, pytopicgram simplifies the investigation of how content spreads, how topics evolve, and how audiences interact on Telegram. The library’s modular architecture ensures flexibility and scalability, making it suitable for diverse applications. This paper describes the design, main features, and illustrative examples that demonstrate pytopicgram’s practical effectiveness for studying public conversations.